Inspirations of the theology of Hans Urs von Balthasar - Jastrzębski, Andrzej (Filozofia Chrześcijańska, 2016)
The article is an attempt at characterizing some selected thinkers, who significantly influenced the theological research of Hans Urs von Balthasar. We refer to the thought of St. Thomas Aquinas, existentialist philosophers such as Søren Kierkegaard, Martin Heidegger, the founder of psychoanalysis - Sigmund Freud, as well as to that of the Russian thinker Nikolai Berdyaev and German philosopher Georg Wilhelm Friedrich Hegel. The intent of the author is to show von Balthasar’s eclectic work, i.e. the analysis and assimilation of new ideas in the main body of the Swiss theologian theory.